Primary pleural hybrid cellular schwannoma/perineurioma: A case report - Soria-Céspedes, Danny; Robles-Vidal, Carlos; Gómez-González, Arturo; Peñaloza-Ramírez, Rosalinda; Ortíz Hidalgo, Carlos Federico (My University, 2014)
Hybrid schwannoma/perineurioma is a recently characterized benign nerve sheath tumor, most commonly affecting the lower limb and limb girdle. Hybrid tumors located in the subcutis of the trunk have not previously been reported to affect the pleura. We describe a 52-year-old man with dyspnea and thoracic pain due to a large mass in the right pleura, histologically composed of densely packed, S-100-positive spindle cells, intermixed with cells containing slender nuclei positive for epithelial membrane antigen, Glut-1, and claudin-1. To our knowledge, this is the first report of hybrid schwannoma/perineurioma in the pleura. Copyright © 2014 The Japanese Respiratory Society. Published by Elsevier B.V. All rights reserved.